2004
DOI: 10.1111/j.1462-2920.2004.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of form IA RubisCO and environmental dissolved inorganic carbon on the δ13C of the clam‐chemoautotroph symbiosis Solemya velum

Abstract: Many nutritive symbioses between chemoautotrophic bacteria and invertebrates, such as Solemya velum, have delta(13)C values of approximately -30 to -35%, considerably more depleted than phytoplankton. Most of the chemoautotrophic symbionts fix carbon with a form IA ribulose 1,5-bisphosphate carboxylase (RubisCO). We hypothesized that this form of RubisCO discriminates against (13)CO(2) to a greater extent than other forms. Solemya velum symbiont RubisCO was cloned and expressed in Escherichia coli, purified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 41 publications
3
63
0
Order By: Relevance
“…The apparent K CO2 for S. velum symbionts (28 M) is lower than CO 2 concentrations measured from sediments where S. velum was collected (up to 200 M [39]). Provided boundary layers and other diffusive distances between the symbionts and their environmental source of CO 2 are small enough to prevent the intracellular CO 2 concentration from being substantially lower than the sediment CO 2 concentration, the rate of symbiont carbon fixation should not be limited by CO 2 availability.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The apparent K CO2 for S. velum symbionts (28 M) is lower than CO 2 concentrations measured from sediments where S. velum was collected (up to 200 M [39]). Provided boundary layers and other diffusive distances between the symbionts and their environmental source of CO 2 are small enough to prevent the intracellular CO 2 concentration from being substantially lower than the sediment CO 2 concentration, the rate of symbiont carbon fixation should not be limited by CO 2 availability.…”
Section: Discussionmentioning
confidence: 82%
“…A carbon flux model, derived to estimate the sizes of the CO 2 concentration gradients between the environment and the symbiont cytosol for R. pachyptila tubeworms (35) 2(s) ] is the concentration of CO 2 within the symbiont cells, ␣ R is the kinetic isotope effect for carbon fixation by S. velum symbiont RubisCO, and ␣ D is the kinetic isotope effect for CO 2 diffusion. Using published values for the isotope ratios of S. velum biomass (0.01088 to 0.01085 [10]) and environmental CO 2 (0.01113 to 0.01108 [39]), as well as for the kinetic isotope effects for S. velum symbiont RubisCO (1.0245 [39]) and diffusion (1.0007 [32]), the calculated symbiont intracellular CO 2 concentration is at least 70% of that present in the bivalve's environment. CO 2 gradients between the environment and the symbiont cells are likely to be mitigated by rapid flushing of the mantle cavity and gill carbonic anhydrase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RubisCO characterization-The responses of enzyme activity to pH and temperature were determined radiometrically by an isotopic disequilibrium technique (Scott et al 2004b). Preliminary experiments indicated that the K CO2 values for these enzymes were quite large, requiring incubations in the presence of very high concentrations of CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent work with high precision methods has indicated that form I enzymes discriminate against 13 C to a greater extent than form II. Form IA RubisCO from the gamma proteobacterial chemolithoautotrophic endosymbionts of the protobranch bivalve Solemya velum has an e value of 24.5% (Scott et al 2004b), whereas form IB RubisCOs from spinach and from the freshwater cyanobacterium Synechococcus PCC6301 have e values of 29% and 22%, respectively (Roeske and O'Leary 1984;Guy et al 1993;McNevin et al 2006). Fractionation by form II RubisCOs from the photosynthetic alpha proteobacterium Rhodospirillum rubrum and from the symbionts of the hydrothermal vent tubeworm Riftia pachyptila is less than that demonstrated by the form I RubisCOs.…”
mentioning
confidence: 99%